Utilization of telepharmacy in the management of hypertension - Ivan Eduku Mozu; Afia Frimpomaa Asare Marfo; John Serbe Marfo; Nana Ofori Adomako; Nana Kwame Ayisi-Boateng; Pauline Boachie-Ansah; Joseph Attakorah; Frances Thelma Owusu-Daaku (Exploratory Research in Clinical and Social Pharmacy, 2023)
Background: Deaths due to cardiovascular diseases is on the rise, with hypertension as its most important risk factor. Effective management of hypertension, however, remains a challenge. Globally, only one in five adults with hypertension have it under control. The situation is worse in sub-Saharan Africa where hypertension prevalence is highest. Telepharmacy presents a great opportunity to enhance the way we address hypertension management. Objectives: This study sought to determine the effectiveness of pharmaceutical care interventions implemented through telepharmacy on medication adherence, practice of therapeutic lifestyles and overall blood pressure control among patients with hypertension. Methods: This was a randomized control trial conducted among individuals with hypertension recruited from two Ghanaian hospitals from May 2022 to December 2022. Patients with confirmed diagnosis of hypertension were recruited and assigned into a control or intervention group. Both groups were followed for six months with the intervention group receiving telepharmacy services in addition to standard clinical care. Outcome measures included changes in blood pressure, medication adherence, lifestyle modifications, identification and resolution of pharmaceutical care issues. Results: One hundred and eighteen (118) patients with hypertension were involved in the study. There was a statistically significant reduction in mean blood pressures for the intervention group after six months (Systolic-148.1 + 23.6, to 134.8 + 13.7, Diastolic- 85.8 + 9.8, to 79.5 + 8.7) (p < 0.05). The proportion of patients with adequately controlled blood pressure increased from 39.0% to 66.1%. There was also an increase in the mean adherence score (p < 0.05). The number of participants who adopted lifestyle modifications such as reducing salt consumption (89.5%) and exercising (77.2%) increased. The majority (87%) of all pharmaceutical care issues were identified and resolved over the six-month period. Conclusion: Telepharmacy service provided via phone calls was effective in improving the control of blood pressure. It also promoted the practice of therapeutic lifestyle modifications, medication adherence and identification of pharmaceutical care issues among patients with hypertension.